Хромосомный гетероморфизм Octolasium lacteum (Oerley, 1885) (Oligochaeta, Lumbricidae) как результат гибридогенеза - Гарбар, А.В.; Онищук, И.П. (Видавничий дім "Академперіодика" НАН України, 2007)
Karyotype Octolasium lacteum (Oerley, 1885) is studied. The chromosomal formula is 2n = = 13m+23sm+2st = 38; the fundamental number is FN = 76; and the total diploid complement length is TCL = 176.91±14.22 µm. The heteromorphism of the ﬁrst chromosome pair which is represented by a large submetacentric and a smaller metacentric is discovered. Spermatogonial meiosis of this species has some violations. Only 12 bivalents (at n = 19) are discovered. The karyotype of this species is supposed to appear as a result of hybridization of the related species with the chromosome numbers 2n = 36 and 2n = 40.